The filterization method to calculate eigenstates - Gogtas, F; Yildiz, AK; BalintKurti, GG (World Scientific Publ Co Pte Ltd, 1997)
We have proposed a new method to calculate low lying eigenstates of Hamiltonian operator for triatomic molecules. The method is a grid method based on continuously pumping flux onto the potential energy surface and gives the wave function overlap ping with prechosen energy of interest. This energy may correspond to a bound state, a resonance or a continuum state. We have calculated several low lying bound state energies and corresponding bound state wave functions for HOCl with HO bond fixed at its equilibrium value.
Keywords: Dependent Schrodinger-Equation; Reactive Scattering; Molecular-Dynamics; Eigenfunctions; State